Conceptual Framework of a Social Entrepreneurship Model in Crowdfunding Platform Towards Communities - Wan Nur Fazni Wan Mohamad Nazarie; Mohd Suffian Mohamed Esa (Penerbit USIM, 2024)
This study attempts to develop a practical model of social entrepreneurship in crowdfunding platforms toward communities. Crowdfunding is a way to raise money from the crowd in order to achieve project goals. Three important elements involves: crowd, project owner and platform. Meanwhile, social entrepreneurship is all about recognizing the social problems and achieving social change by employing entrepreneurial principles, processes and operations. As pandemic of COVID-19 has shown the struggle of people to survive and the challenges caused by the pandemic. Recent studies found that social entrepreneurs can apply as a response to a major crisis in the local community. In other words, social entrepreneurs can become an entity that can help the community to better prepare during crisis. This study proposes the framework that reconceptualizing the concept of the social entrepreneurship in crowdfunding platform toward communities during pandemic. The respondents consist of project owner that do a social project and the funder. This study adopts a mixed-methods approach that is based on interviews, content analysis and surveys by investigating the components of the social entrepreneurship model in crowdfunding platform perspective. The outcome of this study may contribute to developing a model that will enhance the sustainability of social projects among social entrepreneurship